Market based instruments national experiences in environmental sustainability - Kreiser, Larry; Duff, David. 1959-; Milne, Janet E.; Ashiabor, Hope. (Cheltenham, UK Edward Elgar Publishing Limited, 2013)
In the field of environmental policy, there is a widespread tendency to move from command-and-control towards market based instruments that are more efficient and less costly. This book provides a fresh contribution to the literature enlightening the most relevant characteristics of economic tools, with a comprehensive review of experiences in the EU, the Asia-Pacific region and North America. Even if this is a technical book, the language is plain and the comprehension easy. There is much to learn in reading it.--Alberto Majocchi, University of Pavia, Italy. This book contains an impressive collection of papers discussing various aspects of the application of different market based instruments for environmental and climate policy. It covers questions related to the conceptualisation of environmental taxation and national experiences as well as results of modelling exercises from different countries. I highly recommend this book as it discusses the current developments in the application and assessments of market based instruments written by scholars from diverse backgrounds.' - Stefan Speck, European Environment Agency, Denmark. This detailed book explores how market based environmental strategies are used in various countries around the world. It investigates how successful sustainability strategies used by one country can be transferred and used successfully in other countries, with a minimum of new research and experimentation. Leading environmental taxation scholars discuss this question and analyse a set of key case studies. This enriching and detailed book will appeal to policy makers in government, as well as to professors in environmental law, environmental economics and environmental sustainability programmes. Students in these fields will also find much to benefit them in this book.
Less pain, more gain: the potential of carbon pricing to reduce Europe's fiscal deficits / John Ward, Robin Smale, Max Krahé and Jacqueline Cottrell -- Monetary instruments to promote technological innovation -- the German Renewable Energy Act / Monika Böhm -- Providing environmental taxes with an environmental purpose / Tatiana Falcão -- Signaling effects of carbon tax in Sweden: an empirical analysis using a state space model / Yasushi Ito -- Tokyo's greenhouse gas emissions trading scheme: a model for sustainable megacity carbon markets / Sven Rudolph and Takeshi Kawakatsu -- Economic impact analysis on China's environmental tax reform through a static computable general equilibrium analysis / Changbo Qin, Jinnan Wang, Chazhong Ge, Shuting Gao, Qianqian Liu and Yajuan Ren -- The extraterritorial impact of the EU and Australian carbon-restricting reforms / Juscelino F. Colares -- Levelling the playing field or playing on unlevel fields: the industry assistance framework under the European Union ETS, the New Zealand ETS, and Australia's CPM / Elena de Lemos Pinto Aydos -- Assessing British Columbia's carbon tax design: public and stakeholder perspectives / Ekaterina Rhodes and Matt Horne -- Incentives for the use of natural gas powered vehicles in the United States, New Zealand and Australia / Bill Butcher, Hans Sprohge, Rahmat Tavallali and Larry Kreiser.
Includes bibliographical references and index.
Keywords: Environmental policy; Climatic changes -- Government policy; Climatic changes -- Government policy -- European Union countries; Climatic changes -- Government policy -- Pacific Area; Climatic changes -- Government policy -- United States